The end of life experience of older adults in Ireland - Mc Garrigle, Christine; Normand, Charles; May, Peter (The Irish Longitudinal Study on Ageing, Trinity College Dublin, 2017)
This is the first TILDA topic report examining the end-of-life experience of older adults in Ireland. Using interviews completed by family members and friends, the report examines how people died (place and cause of death, health and serious events at end of life), which services and care they received (from both the formal healthcare system and from their families and friends), and factors associated with end-of-life patterns and experiences. This report is based on data from 375 completed end-of-life interviews, representing 73% of 516 confirmed deaths among TILDA participants between Wave 1 (2009) and Wave 3 (2014) of the study. 160 participants for whom an interview was completed died between Wave 1 and Wave 2 (2012), and 215 died between Wave 2 and Wave 3. The average age of death among participants for whom an interview was completed was 78 years and 54% of participants were male. Nearly half (46%) of participant deaths occurred in hospital. Other places included their own home (27%), a hospice (11%) and a nursing home (10%).
Keywords: Ageing